The nature and role of bureaucracy in Bangladesh during the Mujib regime - Aftab Ahmad
Post independence euphoria oftentimes breeds strong sentiments of nationalism, especially among emerging political leaders. As the forefront of forwarding national goals, these leaders are determined to infuse radical ideaologies to obliterate reminants of the earstwhile coloniser. The bureaucrats, on the other hand tend to remain committed to the principles of colonial style administration.The power interplay between political leadership and the bureaucracy often defines the pace and direction of a country's transition, from a colonized to an independent state. Such interplay is depicted in the experience of Bangladesh during Mujib's regime where much importance was attached to political party leadership to th
Keywords: Civil Service -- Bangladesh; Bureaucracy -- Bangladesh